BREAST CANCER EDUCATION AND SELF-EXAMINATION (SADARI) AT CHIBA ISLAMIC CULTURAL CENTER NISHI CHIBA MOSQUE (CICC) JAPAN - Silawati, Vivi; Fikria Ningsih , Nurwalida; Soekmasari , Desy Eka; Pratiwi , Agung; Herawati , Eti; Turasmiyati, Turasmiyati; Rohmah , Siti; Niarsih, Ida (International Journal of Engagement and Empowerment (IJE2), 2025)
Breast cancer is one of the leading causes of death in women worldwide. Early detection through Breast Self-Examination (SADARI) is an important step in efforts to reduce the death rate due to this cancer. Indonesian working women in Japan, most of whom work in the manufacturing and care sectors, face significant health challenges, including low levels of awareness of the importance of early detection of breast cancer. This community service activity aims to increase the awareness and knowledge of Indonesian women workers in Japan about breast cancer and the SADARI technique as a preventive effort. This activity was carried out through health education held at the Chiba Islamic Cultural Center (CICC), Japan, involving 29 mothers from the Indonesian community. The results showed a significant increase in participants' knowledge about breast cancer, risk factors, and SADARI techniques. It is hoped that education about breast cancer and early detection through SADARI can continue to be introduced to Indonesian communities abroad, in order to increase women's empowerment and breast cancer prevention.